Evaluasi Fisik Fasilitas Taman Cerdas Kota Samarinda Menggunakan Metode Mapping Analysis - Yulia Ningsih; Nadia Almira Jordan (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2022)
Urban park is a community necessity that should be equipped with adequate facilities to improve the quality of the urban environment. Taman Cerdas is an urban park in Samarinda City which is intended for children, however, the availability and quality of park elements and facilities are not fully cared for, such as some facilities are damaged and do not meet standards, especially for children. According to public green open space facilities requirements, urban parks need to be supported by good and sufficient quality facilities, so that they are accessible, particularly for children. This study aims to determine the availability and quality conditions of hardscape elements and facilities of Taman cerdas based on the standard of urban parks’ elements and facilities using the mapping analysis method. The results showed that the availability and quality conditions of the facilities, including pedestrian path, park benches, trash cans, play areas, information boards, sports areas, statues, and public toilets, are 22.2% available and appropriate, while 66.6% are available but not suitable, and 11.1% are unavailable.